Inkorporasi Kromium pada Khamir dan Kapang dengan Substrat Dasar Singkong yang Diberi Kromium Anorganik - W D Astuti; T Sutardi; D Evvyernie; T Toharmat (Media Peternakan, 2006)
Organic-chromium (Cr) has higher availability for animals than inorganic-Cr sources. One of organic-Cr sources known is fungi contained high Cr. This organic-Cr was incorporated to fungi protein. Information about the best fungi or microorganisms used in organic-Cr production is still limited. The objective of this experiment was to study organic-Cr production using different kinds of fungi as Cr carrier. Organic-Cr production was conducted in a 4x3 factorial completely randomized experimental design with 3 replications. Four fungi used as carriers in organic-Cr production as the first factor were Saccharomyces cerevisiae, Aspergillus oryzae, Rhizopus oryzae and "ragi tape". The second factor was levels of Cr addition (500, 1000, 1500 mg/kg). Addition of 1000 mg Cr/kg substrate gave the highest Cr incorporation to fungi protein (484 mg/kg) and Cr incorporation efficiency (21.1%). The best fungi used as carrier in organic-Cr production was Rhizopus oryzae which gave the highest Cr incorporation (488 mg/kg) and incorporation efficiency (24.7%). Key words: organic-Cr, production, Saccharomyces cerevisiae, Aspergillus oryzae, Rhyzopus oryzae, "ragi tape"